Hydraulics of border strip irrigation on level or nearly levely rice f ields - Visalakshi K P (Department of Agricultural Engineering, College of Horticulture, 1983)
In Kerala, more than seventy per cent of the double cropped rice fields lie fallow during summer months. Rice cannot be grown during this season because of the limited availability of water and the very low water use efficiency that can be attained during this season. The development of a technology for efficient use of limited water available during summer is necessary to make use of these rice fallows for cultivating crops other than rice. As most of the area is under paddy during first and second crop seasons, the level of the land cannot be disturbed. But now, there is no any satisfactory method of irrigation suitable for irrigating nearly level rice fallows. The objective of this project was to study the hydraulics of border strip irrigation in nearly level lands and to recommend suitable specifications. The experiment was done at the Agronomic Research Station, Chalakudy during 1981-82. It consisted of five replications of four treatments. The treatments were two widths of 4m and 6m combined with two discharge rates of 2 1/sec/m and 4 1/sec/m, the length of strip in all cases being 45m. The surface gradient was 0.03815 per cent in the direction of natural slope. Altogether seven irrigations were given at an interval of seven days. Blackgram seeds were dibbled in the field after the first irrigation and cultural practices as recommended in the package of practices were followed. The time of advance of waterfront, the depth of flow and the time of recession of tail water were observed at every 5m length for each strip. The cutoff length was chosen as 77 per cent from the upstream end. The hydraulic gradient, hydraulic resistance and velocity of flow for each irrigation were determined. The advance and recession curves were drawn. The results of the experiment revealed that a discharge rate of 2 1/sec/m is the best for irrigating nearly level borders of 4m and 6m widths. The depth of irrigation could be limited to 5 cm even in soils having high rate of infiltration. The lower discharge rate of 2 1/sec/m reduced the time of ponding at the downstream end and this minimized the wastage due to deep percolation at the downstream end. Soil erosion in the strip was minimum at this rate of discharge, and long strips upto 45m length in loamy sand could be irrigated with high degree of efficiency. As only a low rate of discharge is required to practice this method, even in areas having limited availability of water, an additional crop can be profitably raised. It is estimated that the water needed to raise one hectare of rice in summer months can be more profitably used to raise about 4 ha. of any other crop. Hence, growing rice during summer season should be discouraged and the land should be utilized to raise other remunerative crops like pulses, oilseeds and vegetables. Now the Government has decided to provide water not only for rice but also for other seasonal crops during the summer months. But now, there is no satisfactory method of irrigation for nearly level fields. Border strip method of irrigation is hardly practiced anywhere in Kerala, even though this is a very popular method in the other parts of India for raising cereals, pulses and oilseeds. However, this method is practiced there on sloping lands. Since the present study revealed that this method can be practiced efficiently on level or nearly level fields, this is best suited for the rice fallows during the dry season. Most of the paddy fields have a mild natural slope in one directions. This slope can be used to advantage by laying the strips in the direction of natural slope. This method can be recommended to the farmers for raising a crop in the rice fallows. The specifications of border strips for nearly level lands are as follows: _______________________________________ Length of border - Upto 45m Width of border - 4 – 6m Rate of flow - 2 1/sec/m Slope - should be laid in the direction of natural slope Height of bunds separating the strips - 20 cm Base width of bunds - 30 cm _______________________________________